Protection of the rights of the Indigenous people by Datuok (Chief of the tribe / Ninik Mamak) as a traditional leader in the village of Sipungguk Bangkinang, Kampar Regency - Darnia, Meriza Elpha (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
-